2014
DOI: 10.1177/0961203314551812
|View full text |Cite
|
Sign up to set email alerts
|

Renal biopsy in the management of lupus nephritis during pregnancy

Abstract: The differential diagnosis of proteinuria and hematuria in pregnancy is broad and includes active lupus nephritis. Identification of the correct diagnosis often has a profound therapeutic impact on not only the mother but also the fetus. To date, relatively few reports exist on the role of renal biopsy during pregnancy among women with systemic lupus erythematosus (SLE). We present a case series of 11 pregnant women with SLE who underwent a renal biopsy to evaluate a presumptive flare of lupus nephritis. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Increased risk for (i) maternal disease activity (RR 2.1 for subsequent flare during pregnancy and puerperium); 14 (ii) hypertensive complications (OR 1.8 for PE); 15 (iii) fetal morbidity and mortality (OR 5.7 for pregnancy loss, 16 3.5 for IUGR 17 6.5 for preterm delivery) 14 15 17-22 Lupus nephritis (history or active at conception †)…”
Section: Disease-related Risk Factorsmentioning
confidence: 99%
“…Increased risk for (i) maternal disease activity (RR 2.1 for subsequent flare during pregnancy and puerperium); 14 (ii) hypertensive complications (OR 1.8 for PE); 15 (iii) fetal morbidity and mortality (OR 5.7 for pregnancy loss, 16 3.5 for IUGR 17 6.5 for preterm delivery) 14 15 17-22 Lupus nephritis (history or active at conception †)…”
Section: Disease-related Risk Factorsmentioning
confidence: 99%
“…However, all these measures have limitations and differentiation may be extremely difficult. Renal biopsy could guide management in selected cases and is safe in experienced hands 41 . However, at times, delivery of the baby may be the only definitive answer.…”
Section: Pre-eclampsia In Sle Pregnancymentioning
confidence: 99%
“…Renal biopsy is a valuable research tool for accurate characterization of LN, but it is usually avoided during pregnancy considering technical difficulties of this procedure in pregnant women. Either way, a recent study found that renal biopsy provides useful information for the management of patients with LN during pregnancy [ 60 ].…”
Section: Lupus Flares During Pregnancymentioning
confidence: 99%